In vitro model of bacterial biofilm mineralization in complex humid environments: a proof of concept study - Zorzetto, L.; Hammer, S.; Paris, S.; Bidan, C. M. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundBacteria in physiological environments can generate mineralizing biofilms, which are associated with diseases like periodontitis or kidney stones. Modelling complex environments presents a challenge for the study of mineralization in biofilms. Here, we developed an experimental setup which could be applied to study the fundamental principles behind biofilm mineralization on rigid substrates, using a model organism and in a tailored bioreactor that mimics a humid environment. We developed a simple yet effective method to produce rigid specimens with the desired shape.Materials and MethodsTo simulate humid growth conditions, rigid specimens were conditioned with human saliva, inoculated with the chosen model bacterial strain and placed in a chamber with continuous drop-wise supply of nutritious media. The preconditioning stage did not affect significantly the bacteria proliferation, but considering this option was instrumental to future evolutions of the model, where saliva could be substituted with other substances (e.g., urine, plasma or antimicrobial solutions). Two different growth media were used: a control medium with nutritious substances and a mineralizing medium consisting in control medium supplemented with mineral precursors. Both the specimen shape and the bioreactor designs resulted from an optimization process thoroughly documented in this work. As a proof of concept, we showed that it is possible to locate the bacteria and minerals using confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM).ResultsWe achieved an in vitro model representative of the conditions of growth and mineralization of biofilms in humid environments on a rigid substrate: something between the traditional solid-air and solid-liquid interface models.ConclusionSuch model will be useful to understand fundamental mechanisms happening in complex environments.